O sistema permanente de avaliação da educação básica do Ceará (SPAECE): avaliação ou política de resultado? Uma releitura do mundo para reensinar a palavra como prática da liberdade - Sousa, Jonas Serafim de (2025)
Assessment is a way of understanding the process of integral formation of the person through the influence of different types of knowledge, which produce the development of human performance and ability for decision-making. In this context, the general objective of this research was: to evaluate the Permanent Assessment System for Basic Education in Ceará (SPAECE) in the context of 9th grade students of a school in Region V with the lowest learning index, in the period of 2023, perceiving the dimension of the assessment problem and pointing out possible solutions. Regarding the specific objectives, the following were of interest: 1) To analyze the assessment process of 9th grade students of the investigated school, with a low learning index by SPAECE, based on the teaching methodology applied by the school's teachers; 2) To investigate the study process of 9th grade students of the school in question and under what conditions they carry out the SPAECE assessment, based on the activities carried out by the teachers; 3) Propose study workshops on SPAECE, in order to make public education policy a contextualized reality with the participation of teachers, students and their families, as an incentive for learning in 9th grade elementary school classes, to improve the quality of comprehensive education in favor of social well-being. The path followed in search of answers initially took place through bibliographic and documentary research. Then, fieldwork emerged as essential, since semi-structured interviews were directed to teachers. Regarding the evaluative perspective, it was necessary to consider the sociopolitical and cultural context in the evaluation of public policies, especially in light of the historical-critical pedagogy discussed by Saviani (2024), Luckesi (2011) and libertarian education, which Freire (2015; 2024) defends, strands that, contrary to evaluation as control, understand it as an instrument of change, especially among the popular classes. Among the results found, SPAECE did not respond to comprehensive training, and when it reaches schools, it comes with many demands on management. Although knowing that it does not promote social well-being, and therefore does not bring effectiveness or efficiency, much less effective impacts on the transformation of school life, the boldness here proposes this change, from the perspective of public education policy. This assessment only considers skills and abilities in Portuguese and Mathematics, to monitor educational policies and associate financial incentives. In this investigation, I saw that the satisfactory results of the assessments prepared by teachers in context with the reality of the students, were more satisfactory in the process of school learning in a comprehensive way, unlike a policy of results.